Cobalt carbonate, cobalt tetroxide, preparation method, positive electrode material and lithium battery
By preparing cobalt tetroxide with uniform pore distribution and narrow particle size distribution, the problem of poor particle consistency between the positive electrode materials of existing lithium-ion batteries is solved, and the cycle stability and capacity of the battery are improved.
Patent Information
- Application Number
- CN202211347174.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-10-31
AI Technical Summary
The particle size distribution of the positive electrode materials of existing lithium-ion batteries is wide, and the consistency between particles is poor, which leads to an increase in reaction resistance, a decrease in battery capacity, and a small particle size may lead to overburn, affecting the quality of the positive electrode.
It provides a kind of cobalt tetroxide, which has a porous interior, a uniform pore distribution, a fitted R2 value of the porosity distribution>0.9, and a range of particle size distribution (D90-D10)/(D90+D10) is 0.20-0.35. By preparing cobalt carbonate Sintering was performed to obtain the cobalt tetroxide.
The reactivity and uniformity of the positive electrode material and the crystal growth are improved, the stability of the positive electrode material structure is enhanced, and the cycle stability and capacity of the battery are improved.
Smart Images

Figure CN116262634B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to cobalt carbonate, cobalt tetroxide and preparation methods, positive electrode materials and lithium batteries. Background Art
[0002] As 3C products are updated more and more frequently, "lighter, thinner and more durable" is a development trend of 3C products, which puts higher requirements on the energy density and stability of lithium-ion batteries. At present, the energy density of batteries is mainly improved by increasing the cut-off voltage and compaction density. Usually, researchers use a variety of element doping methods to modify lithium cobalt oxide materials to improve their stability during high-voltage charging and discharging.
[0003] The existing products are affected by the preparation method, with a wide particle size distribution and poor consistency between particles, which may cause defects such as increased reaction resistance. The voltage applied to the particles in the electrode is uneven. If the charge and discharge are repeated, the microparticles will selectively deteriorate, resulting in a decrease in battery capacity. In addition, when the particle size of the secondary particles is too small, it may lead to an increase in fine powder, which will cause overburning during the positive electrode sintering process, thus affecting the quality of the positive electrode. Summary of the invention
[0004] In order to solve the above-mentioned defects, the purpose of the present application is to provide a cobalt oxide with a relatively narrow particle size distribution and high consistency between particles, so as to obtain a positive electrode material with better performance.
[0005] To achieve the above objectives, the present application provides a cobalt tetroxide, which is porous inside, has a uniform pore distribution, and a porosity distribution fitting R 2 value>0.9; the particle size distribution of cobalt oxide (D90-D10) / (D90+D10) ranges from 0.20 to 0.35.
[0006] Preferably, the pore size of cobalt tetraoxide is 1 to 25 nm;
[0007] Preferably, the particle size distribution of cobalt oxide (D90-D10) / (D90+D10) is in the range of 0.20 to 0.30;
[0008] Preferably, the particle size D50 of cobalt tetraoxide is in the range of 15 to 19 μm;
[0009] Preferably, the specific surface area of cobalt tetraoxide is 2 to 4 m 2 / g;
[0010] Preferably, the tap density of cobalt oxide is 2.3 to 2.9 g / cm 3 .
[0011] Preferably, the cobalt oxide includes doping elements, and the total content of the doping elements is 0 to 3%;
[0012] Preferably, the doping element is selected from one or more of Al, Mg, Ni, and Mn;
[0013] Preferably, the doping mass contents of the doping elements are: Al: 0.40-1.20%, Mg: 0.10-0.50%, Ni: 0.10-3.00%, and Mn: 0.10-3.00%.
[0014] The present application also provides a cobalt carbonate for preparing the above-mentioned cobalt tetroxide, wherein the particle size distribution (D90-D10) / (D90+D10) of the cobalt carbonate is in the range of 0.20 to 0.35; and the particle size D50 of the cobalt carbonate is in the range of 19 to 24 μm.
[0015] The present application also provides a method for preparing cobalt carbonate, comprising:
[0016] Preparation of seed crystals: adding a cobalt salt solution and a precipitant solution into a reaction kettle containing a base solution, and reacting in an intermittent production process to obtain seed crystals, wherein the seed crystals have a particle size of 4 to 6 μm, and a particle size distribution of the seed crystals (D90-D10) / (D90+D10) in the range of 0.30 to 0.50;
[0017] Seed crystal growth: on the basis of obtaining the seed crystal, continue to add the cobalt salt solution and the precipitant solution into the reactor, continue the reaction until the target particle size is reached, and obtain the cobalt carbonate slurry;
[0018] Washing: The cobalt carbonate slurry is washed and dehydrated to obtain cobalt carbonate.
[0019] Preferably, during the process of preparing the seed crystals, the molar ratio of the cobalt salt solution to the precipitant solution is 1:3-4;
[0020] Preferably, the intermittent production process comprises: firstly adding the cobalt salt solution to the reactor at a flow rate of 1% to 2% of the volume of the reactor / h to react for 2 to 4 hours, stopping the feeding and stirring for 0.5 to 2 hours, and then adding the cobalt salt solution to the reactor at a flow rate of 2% to 3% of the volume of the reactor / h to continue reacting for 2 to 4 hours;
[0021] Preferably, during the seed crystal growth process, the molar ratio of the cobalt salt solution to the precipitant solution is 1:2.5-3.5, and the flow rate of the cobalt salt solution is 3%-6% / h of the volume of the reactor.
[0022] Preferably, the cobalt salt solution is selected from a cobalt sulfate solution and / or a cobalt chloride solution; the precipitant solution is selected from an ammonium bicarbonate solution and / or a sodium carbonate solution; and the base solution is selected from an ammonium bicarbonate solution and / or a sodium carbonate solution;
[0023] Preferably, the cobalt concentration in the cobalt salt solution is 90-130 g / L, the concentration of the precipitant solution is 190-230 g / L; the concentration of the base solution is 5-50 g / L;
[0024] Preferably, the cobalt salt solution includes a doping element, and the doping element is selected from one or more of Al, Mg, Ni, and Mn;
[0025] Preferably, the doping mass contents of the doping elements in the cobalt carbonate are respectively:
[0026] Al: 0.26~0.70%, Mg: 0.06~0.33%, Ni: 0.06~2.00%, Mn: 0.06~2.00%.
[0027] The present application also provides a method for preparing cobalt tetroxide, comprising:
[0028] Providing the above-mentioned cobalt carbonate, or the cobalt carbonate prepared by the above-mentioned method for preparing cobalt carbonate;
[0029] Sintering cobalt carbonate to obtain cobalt tetroxide;
[0030] Preferably, the sintering temperature is 700-850°C;
[0031] Preferably, when a rotary kiln is used for sintering, the induced air velocity in the furnace tube of the rotary kiln is 0.5 to 5 m / s.
[0032] The present application also provides a positive electrode material, which is lithium cobalt oxide obtained by calcining the above-mentioned cobalt trioxide and a lithium source;
[0033] Preferably, the molar ratio of the lithium source to cobalt tetroxide is 1 to 1.05;
[0034] Preferably, the calcination temperature is 900-1200° C., and the calcination time is 20-30 hours.
[0035] The present application also provides a lithium battery, comprising the above-mentioned positive electrode material.
[0036] Compared with the prior art, the beneficial effects of this application include:
[0037] The cobalt tetroxide provided in the present application is porous inside, and the pores are evenly distributed, and the particle size distribution (D90-D10) / (D90+D10) of the cobalt tetroxide is in the range of 0.20 to 0.35. The particle size distribution is relatively narrow, and the consistency between particles is high, which is beneficial to the reaction activity of the prepared positive electrode material and the uniformity of crystal growth, improves the stability of the positive electrode material structure, and helps to improve the cycle stability of the battery. The pores inside the particles are uniform, which is beneficial to the uniform distribution of the doping elements throughout the particles, which is beneficial to the stability of the rear-end positive electrode material structure and improves the battery cycle stability. The narrow particle size distribution and the uniform distribution of pores inside the particles are beneficial to the controllability of the crystal growth and particle size distribution of the rear-end positive electrode material, improve the stability of the subsequent compaction of the positive electrode material, and help to improve the capacity and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0039] Figure 1 This is a scanning electron microscope morphology image of the cobalt tetroxide prepared in Example 1;
[0040] Figure 2 This is a scanning electron microscope morphology image of the cobalt tetroxide prepared in Example 2;
[0041] Figure 3 This is a scanning electron microscope morphology image of the cobalt tetroxide prepared in Example 3;
[0042] Figure 4 This is a scanning electron microscope morphology image of the positive electrode material prepared in Example 3;
[0043] Figure 5 This is a scanning electron microscope morphology image of the cobalt tetroxide prepared in Example 4;
[0044] Figure 6 This is a scanning electron microscope morphology image of the cobalt tetroxide prepared in Comparative Example 1;
[0045] Figure 7 This is a scanning electron microscope morphology image of the cobalt tetroxide prepared in Comparative Example 2;
[0046] Figure 8 This is a scanning electron microscope morphology image of the positive electrode material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0047] As used herein:
[0048] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0049] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0050] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0051] In these examples, parts and percentages are by mass unless otherwise indicated.
[0052] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0053] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0054] The present application provides a cobalt tetraoxide, which is porous inside, has a uniform pore distribution, and a porosity distribution fitting R 2Value> 0.9; the particle size distribution of cobalt oxide (D90-D10) / (D90+D10) ranges from 0.20 to 0.35. Cobalt oxide is the raw material for preparing lithium cobalt oxide positive electrode materials. Cobalt oxide and lithium source are calcined to obtain lithium cobalt oxide. The performance of cobalt oxide determines the performance of lithium cobalt oxide positive electrode materials, which is inherited.
[0055] The porosity distribution fitting R of the cobalt tetraoxide in this application 2 Value>0.9, porosity distribution fitting R 2 It is used to indicate the uniformity of pore distribution. The specific verification steps are as follows:
[0056] Step 1: Treat a single cobalt oxide particle as a sphere, and divide the circle into n (n≥3) concentric circles according to the cross-section circle of the sphere;
[0057] Step 2: Calculate the area of each concentric circle and the difference between the areas of adjacent concentric circles, as well as the pore area of the corresponding area;
[0058] Step 3: Calculate the change x of the cross-sectional area in different regions and the change y of the pore area in the corresponding region;
[0059] Step 4: Establish a linear relationship between x and y and calculate the correlation coefficient R 2 ;
[0060] When R 2 When R > 0.9, the pore distribution is considered uniform. 2 When R is between 0.90 and 0.95, the pore distribution is considered to be relatively uniform. 2 When ≥0.95, the pore distribution is considered to be highly uniform;
[0061] When R 2 When ≤0.9, the pore distribution is considered to be uneven.
[0062] Among them, D10 means the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 10%, and its physical meaning is that 10% of the particles have a smaller particle size than it; D90 means the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 90%, and its physical meaning is that 90% of the particles have a smaller particle size than it; both D10 and D90 can be measured by Malvern 3000 laser particle size tester; (D90-D10) / (D90+D10) represents the distribution range of particle size, the smaller the value, the more uniform the particle size distribution.
[0063] The particle size distribution (D90-D10) / (D90+D10) of tricobalt tetroxide may be, for example, in the range of 0.20 to 0.35, or 0.20 to 0.30, or 0.25 to 0.35, and more specifically, in the range of 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34 or 0.35. Preferably, the particle size distribution (D90-D10) / (D90+D10) of tricobalt tetroxide is in the range of 0.20 to 0.30.
[0064] The cobalt tetroxide provided in the present application is porous inside, and the pores are evenly distributed, and the particle size distribution (D90-D10) / (D90+D10) of the cobalt tetroxide is in the range of 0.20 to 0.35. The particle size distribution is relatively narrow, and the consistency between particles is high, which is beneficial to the reaction activity of the prepared positive electrode material and the uniformity of crystal growth, improves the stability of the positive electrode material structure, and helps to improve the cycle stability of the battery. The pores inside the particles are uniform, which is beneficial to the uniform distribution of the doping elements throughout the particles, which is beneficial to the stability of the rear-end positive electrode material structure and improves the battery cycle stability. The narrow particle size distribution and the uniform distribution of pores inside the particles are beneficial to the controllability of the crystal growth and particle size distribution of the rear-end positive electrode material, improve the stability of the subsequent compaction of the positive electrode material, and help to improve the capacity and cycle stability of the battery.
[0065] Preferably, the pore size of cobalt oxide is 1 to 25 nm, and the smaller the pore size, the higher the particle density under similar specific surface area. For example, the pore size of cobalt oxide can be 1.0 to 5.0 nm, 3.0 to 10.0 nm, 6.0 to 15.0 nm, or 12.0 to 25 nm. In a further example, the pore size of cobalt oxide can be 1.0 nm, 2.0 nm, 3.0 nm, 4.0 nm, 5.0 nm, 6.0 nm, 7.0 nm, 8.0 nm, 9.0 nm, 10.0 nm, 11.0 nm, 12.0 nm, 13.0 nm, 14.0 nm, 15.0 nm, 16.0 nm, 17.0 nm, 18.0 nm, 19.0 nm, 20.0 nm, 21.0 nm, 22.0 nm, 23.0 nm, 24.0 nm, or 25.0 nm.
[0066] Preferably, the particle size D50 of tricobalt tetroxide ranges from 15 to 19 μm. For example, the median particle size of tricobalt tetroxide may be 15 to 17 μm, 16 to 18 μm, or 17 to 19 μm. In a further example, the median particle size of tricobalt tetroxide may be 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, or 19 μm.
[0067] Preferably, the specific surface area of cobalt tetraoxide is 2 to 4 m 2 / g. For example, the specific surface area of cobalt tetraoxide can be 2.0 to 3.0 m 2 / g, 2.5~3.5m 2 / g, or 2.5~4.0m 2 / g. In a further example, the specific surface area of cobalt tetraoxide can be 2.0m 2 / g, 3.0m 2 / g or 4.0m 2 / g.
[0068] Preferably, the tap density of cobalt oxide is 2.3 to 2.9 g / cm 3 For example, the tap density of cobalt oxide can be 2.3 to 2.7 g / cm 3 2.4~2.8g / cm 3 2.5~2.6g / cm 3 , or 2.6~2.9g / cm 3 In a further example, the tap density of cobalt oxide can be 2.30 g / cm 3 , 2.35g / cm 3 , 2.40g / cm 3 , 2.45g / cm 3 , 2.50g / cm 3 , 2.55g / cm 3 , 2.60g / cm 3 , 2.65g / cm 3 , 2.70g / cm 3 , 2.75g / cm 3 , 2.80g / cm 3 , 2.85g / cm 3 or 2.90g / cm 3 .
[0069] Preferably, the cobalt oxide includes doping elements, and the total content of the doping elements is 0-3%.
[0070] Preferably, the doping element is selected from one or more of Al, Mg, Ni and Mn.
[0071] Preferably, the doping mass contents of the doping elements are: Al: 0.40-1.20%, Mg: 0.10-0.50%, Ni: 0.10-3.00%, and Mn: 0.10-3.00%.
[0072] The present application also provides a cobalt carbonate for preparing the above-mentioned cobalt tetroxide, wherein the particle size distribution (D90-D10) / (D90+D10) of the cobalt carbonate is in the range of 0.20 to 0.35; and the particle size D50 of the cobalt carbonate is in the range of 19 to 24 μm.
[0073] The present application also provides a method for preparing cobalt carbonate, comprising:
[0074] Preparation of seed crystals: adding a cobalt salt solution and a precipitant solution into a reactor containing a base liquid, and reacting in an intermittent production process to obtain seed crystals, the particle size of the seed crystals being 4 to 6 μm, and the particle size distribution of the seed crystals (D90-D10) / (D90+D10) being in the range of 0.30 to 0.50.
[0075] Specifically, the cobalt salt solution is selected from a cobalt sulfate solution and / or a cobalt chloride solution; the precipitant solution is selected from an ammonium bicarbonate solution and / or a sodium carbonate solution; and the base solution is selected from an ammonium bicarbonate solution and / or a sodium carbonate solution;
[0076] The cobalt concentration in the cobalt salt solution is 90-130 g / L, for example, it can be (90, 91, 93, 95, 96, 98, 100, 102, 105, 106, 108, 110, 112, 115, 116, 118, 120, 122, 123, 126, 128 or 130) g / L.
[0077] The concentration of the precipitant solution is 190-230 g / L; the concentration of the base solution is 5-50 g / L.
[0078] Preferably, the cobalt salt solution includes a doping element, and the doping element is selected from one or more of Al, Mg, Ni, and Mn;
[0079] Preferably, the doping mass contents of the doping elements in the cobalt carbonate are respectively:
[0080] Al: 0.26~0.70%, Mg: 0.06~0.33%, Ni: 0.06~2.00%, Mn: 0.06~2.00%.
[0081] Preferably, in the process of preparing the seed crystals, the molar ratio of the cobalt salt solution to the precipitant solution is 1:3 to 4. For example, it may be 1:3, or 1:3.5, or 1:4.
[0082] Preferably, the intermittent production process comprises: firstly adding the cobalt salt solution into the reactor at a flow rate of 1% to 2% of the volume of the reactor / h to react for 2 to 4 hours, stopping the feeding and stirring for 0.5 to 2 hours, and then adding the cobalt salt solution into the reactor at a flow rate of 2% to 3% of the volume of the reactor / h to continue the reaction for 2 to 4 hours.
[0083] Seed crystal growth: on the basis of obtaining the seed crystal, continue to add the cobalt salt solution and the precipitant solution into the reactor, continue the reaction to the target particle size, and obtain the cobalt carbonate slurry.
[0084] Preferably, during the seed crystal growth process, the molar ratio of the cobalt salt solution to the precipitant solution is 1:2.5-3.5, and the flow rate of the cobalt salt solution is 3%-6% / h of the volume of the reactor.
[0085] Washing: The cobalt carbonate slurry is washed and dehydrated to obtain cobalt carbonate.
[0086] The present application also provides a method for preparing cobalt tetroxide, comprising:
[0087] Providing the above-mentioned cobalt carbonate, or the cobalt carbonate prepared by the above-mentioned method for preparing cobalt carbonate;
[0088] Sintering cobalt carbonate to obtain cobalt tetroxide;
[0089] Preferably, the sintering temperature is 700-850°C;
[0090] Preferably, when a rotary kiln is used for sintering, the induced air velocity in the furnace tube of the rotary kiln is 0.5 to 5 m / s.
[0091] The present application also provides a positive electrode material, which is lithium cobalt oxide obtained by calcining the above-mentioned cobalt trioxide and a lithium source;
[0092] Preferably, the molar ratio of the lithium source to cobalt tetroxide is 1 to 1.05;
[0093] Preferably, the calcination temperature is 900-1200° C., and the calcination time is 20-30 hours.
[0094] The present application also provides a lithium battery, comprising the above-mentioned positive electrode material.
[0095] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0096] Example 1
[0097] Step 1: Prepare the solution
[0098] Cobalt sulfate solution, aluminum sulfate solution, nickel sulfate solution and manganese sulfate solution are mixed to prepare a cobalt salt solution doped with aluminum, nickel and manganese, wherein the cobalt concentration in the cobalt salt solution is 90 g / L, the aluminum concentration is 1.12 g / L, the nickel concentration is 0.3 g / L and the manganese concentration is 0.375 g / L; 190 g / L of ammonium bicarbonate solution is prepared.
[0099] Step 2: Synthesis of doped cobalt carbonate
[0100] 1. Opening the kettle: Add 5% of the volume of the reactor to the reactor ammonium bicarbonate solution (concentration 10g / L) as the bottom liquid. At 300r / min, the doped cobalt solution and ammonium bicarbonate solution prepared in step 1 are pumped into the reactor at a molar ratio of 1:3 for reaction. The flow rate of the cobalt salt solution is 1% / h of the volume of the reactor. The reaction time is 2h. Stop feeding and stirring for 0.5h, and continue feeding and reacting for 2h with the flow rate of the cobalt salt being 2% / h of the volume of the reactor. The seed particle size D50 is 4.3μm, and the particle size distribution (D90-D10) / (D90+D10) is 0.35.
[0101] 2. Growth stage: Based on step 1, the feeding reaction is continued. The flow rate of the cobalt liquid is 3% / h of the volume of the reactor. The doped cobalt liquid and the ammonium bicarbonate solution are pumped into the reactor at a molar ratio of 1:2.5 for reaction. When the slurry in the growth reactor reaches the upper limit, the supernatant is removed by a concentrator. The reaction is continued until the target particle size D50 is 19.8 μm to obtain a doped cobalt carbonate slurry, which is then placed in an aging tank for temporary storage.
[0102] Step 3: Washing
[0103] The doped cobalt carbonate slurry in the aging tank is pumped into a centrifuge, and pure water is introduced for washing, and then centrifuged and dehydrated to obtain a doped cobalt carbonate wet material. The particle size distribution of the cobalt carbonate in Example 1 is (D90-D10) / (D90+D10) is 0.26.
[0104] Step 4: Calcination
[0105] The doped cobalt carbonate is calcined in a rotary kiln to obtain doped cobalt tetroxide. The temperature of the high temperature zone of the rotary kiln is 800°C, and the induced wind speed in the furnace tube is 0.5m / s.
[0106] The specific parameters of the cobalt tetroxide prepared in Example 1 are shown in Table 1, and the scanning electron microscope morphology of cobalt tetroxide is shown in Figure 1 .
[0107] The cobalt trioxide obtained in Example 1 and lithium carbonate were uniformly mixed at a Li / Me molar ratio of 1.05:1, and calcined at 1060° C. for 24 h to prepare the lithium cobalt oxide positive electrode material of Example 1.
[0108] Example 2
[0109] Step 1: Prepare the solution
[0110] The cobalt chloride solution and the aluminum sulfate solution are mixed to prepare an aluminum-doped cobalt salt solution, wherein the cobalt concentration in the cobalt salt solution is 130 g / L and the aluminum concentration is 1.62 g / L; and 230 g / L of ammonium bicarbonate solution is prepared.
[0111] Step 2: Synthesis of doped cobalt carbonate
[0112] 1. Opening the kettle: Add 30% of the volume of the reactor to the reactor as the base liquid ammonium bicarbonate solution (concentration 50g / L). At 200r / min, the doped cobalt solution and ammonium bicarbonate solution prepared in step 1 are pumped into the reactor at a molar ratio of 1:4 for reaction. The flow rate of the cobalt salt solution is 2% / h of the volume of the reactor. The reaction time is 4h. Stop feeding and stirring for 2h, and continue feeding and reacting for 4h with the flow rate of the cobalt salt being 3% / h of the volume of the reactor. The seed particle size D50 is 5.2μm, and the particle size distribution (D90-D10) / (D90+D10) is 0.43.
[0113] 2. Growth stage: Based on step 1, the feeding reaction is continued. The flow rate of cobalt liquid is 6% / h of the volume of the reactor. The doped cobalt liquid and ammonium bicarbonate solution are pumped into the reactor at a molar ratio of 1:3.5 for reaction. When the slurry in the growth reactor reaches the upper limit, the supernatant is removed by a concentrator, and the reaction is continued until the target particle size D50 is 21.5 μm to obtain a doped cobalt carbonate slurry, which is then placed in an aging tank for temporary storage.
[0114] Step 3: Washing
[0115] The doped cobalt carbonate slurry in the aging tank is pumped into a centrifuge, and pure water is introduced for washing, and then centrifuged and dehydrated to obtain a doped cobalt carbonate wet material. The particle size distribution of the cobalt carbonate in Example 2 is (D90-D10) / (D90+D10) is 0.31.
[0116] Step 4: Calcination
[0117] The doped cobalt carbonate is calcined in a rotary kiln to obtain doped cobalt tetroxide. The temperature of the high temperature zone of the rotary kiln is 700°C, and the induced wind speed in the furnace tube is 5m / s.
[0118] The specific parameters of the cobalt tetroxide prepared in Example 2 are shown in Table 1, and the scanning electron microscope morphology of cobalt tetroxide is shown in Figure 2 .
[0119] The cobalt trioxide obtained in Example 2 and lithium carbonate were uniformly mixed at a Li / Me molar ratio of 1.05:1, and calcined at 1060° C. for 24 h to prepare the lithium cobalt oxide positive electrode material of Example 2.
[0120] Example 3
[0121] Step 1: Prepare the solution
[0122] The cobalt chloride solution and the aluminum sulfate solution are mixed to prepare an aluminum-doped cobalt salt solution, wherein the cobalt concentration in the cobalt salt solution is 110 g / L and the aluminum concentration is 1.375 g / L; and 210 g / L of ammonium bicarbonate solution is prepared.
[0123] Step 2: Synthesis of doped cobalt carbonate
[0124] 1. Opening the kettle: Add 15% of the volume of the reactor to the reactor ammonium bicarbonate solution (concentration 30g / L) as the bottom liquid. At 300r / min, the doped cobalt solution and ammonium bicarbonate solution prepared in step 1 are pumped into the reactor at a molar ratio of 1:3.54 for reaction. The flow rate of the cobalt salt solution is 1.5% / h of the volume of the reactor. The reaction time is 3h. Stop feeding and stirring for 1h, and continue feeding and reacting for 3h with the flow rate of the cobalt salt being 2.5% / h of the volume of the reactor. The seed particle size D50 is 4.6μm, and the particle size distribution (D90-D10) / (D90+D10) is 0.35.
[0125] 2. Growth stage: Based on step 1, the feeding reaction is continued. The flow rate of cobalt liquid is 4.5% of the volume of the reactor. The doped cobalt liquid and ammonium bicarbonate solution are pumped into the reactor at a molar ratio of 1:3 for reaction. When the slurry in the growth reactor reaches the upper limit, the supernatant is removed by a concentrator. The reaction is continued until the target particle size D50 is 21.0 μm to obtain a doped cobalt carbonate slurry, which is then placed in an aging tank for temporary storage.
[0126] Step 3: Washing
[0127] The doped cobalt carbonate slurry in the aging tank is pumped into a centrifuge, and pure water is introduced for washing, and then centrifuged and dehydrated to obtain a doped cobalt carbonate wet material. The particle size distribution of the cobalt carbonate in Example 3 is (D90-D10) / (D90+D10) is 0.26.
[0128] Step 4: Calcination
[0129] The doped cobalt carbonate is calcined in a rotary kiln to obtain doped cobalt tetroxide. The temperature of the high temperature zone of the rotary kiln is 750°C, and the induced wind speed in the furnace tube is 3m / s.
[0130] The specific parameters of the cobalt tetroxide prepared in Example 3 are shown in Table 1, and the scanning electron microscope morphology of cobalt tetroxide is shown in Figure 3 .
[0131] The cobalt trioxide obtained in Example 3 and lithium carbonate were mixed evenly at a Li / Me molar ratio of 1.05:1, and calcined at 1060° C. for 24 h to prepare the lithium cobalt oxide positive electrode material of Example 3. The scanning electron microscope morphology result is shown in FIG. Figure 4 shown.
[0132] Example 4
[0133] Step 1: Prepare the solution
[0134] The cobalt chloride solution and the aluminum sulfate solution are mixed to prepare an aluminum-doped cobalt salt solution, wherein the cobalt concentration in the cobalt salt solution is 90 g / L and the aluminum concentration is 1.125 g / L; and 190 g / L of ammonium bicarbonate solution is prepared.
[0135] Step 2: Synthesis of doped cobalt carbonate
[0136] 1. Opening the kettle: Add 5% of the volume of the reactor to the reactor ammonium bicarbonate solution (concentration 10g / L) as the bottom liquid. At 300r / min, the doped cobalt solution and ammonium bicarbonate solution prepared in step 1 are pumped into the reactor at a molar ratio of 1:3 for reaction. The flow rate of the cobalt salt solution is 1% / h of the volume of the reactor. The reaction time is 2h. Stop feeding and stirring for 0.5h, and continue feeding and reacting for 2h with the flow rate of the cobalt salt being 3% / h of the volume of the reactor. The seed particle size D50 is 4.5μm, and the particle size distribution (D90-D10) / (D90+D10) is 0.42.
[0137] 2. Growth stage: Based on step 1, the feed reaction is continued. The flow rate of cobalt liquid is 3% / h of the volume of the reactor. The doped cobalt liquid and ammonium bicarbonate solution are pumped into the reactor at a molar ratio of 1:2.5 for reaction. When the slurry in the growth reactor reaches the upper limit, the supernatant is removed by a concentrator. The reaction is continued until the target particle size D50 is 21.0 μm to obtain a doped cobalt carbonate slurry, which is then placed in an aging tank for temporary storage.
[0138] Step 3: Washing
[0139] The doped cobalt carbonate slurry in the aging tank is pumped into a centrifuge, and pure water is introduced for washing, and then centrifuged and dehydrated to obtain a doped cobalt carbonate wet material. The particle size distribution of the cobalt carbonate in Example 4 is (D90-D10) / (D90+D10) is 0.31.
[0140] Step 4: Calcination
[0141] The doped cobalt carbonate is calcined in a rotary kiln to obtain doped cobalt tetroxide. The temperature of the high temperature zone of the rotary kiln is 750°C, and the induced wind speed in the furnace tube is 0.5m / s.
[0142] The specific parameters of the cobalt tetroxide prepared in Example 4 are shown in Table 1, and the scanning electron microscope morphology of cobalt tetroxide is shown in Figure 5 .
[0143] The cobalt trioxide obtained in Example 4 was mixed evenly with lithium carbonate at a Li / Me molar ratio of 1.05:1, and calcined at 1060° C. for 24 h to prepare the lithium cobalt oxide positive electrode material of Example 4.
[0144] Comparative Example 1
[0145] Step 1: Prepare the solution
[0146] The cobalt chloride solution and the aluminum sulfate solution are mixed to prepare an aluminum-doped cobalt salt solution, wherein the cobalt concentration in the cobalt salt solution is 100 g / L and the aluminum concentration is 1.25 g / L; and 210 g / L of ammonium bicarbonate solution is prepared.
[0147] Step 2: Synthesis of doped cobalt carbonate
[0148] 1. Opening the kettle: Add 50% of the volume of the reactor into the reactor as the base liquid ammonium bicarbonate solution (concentration 100g / L). Pump the cobalt solution prepared in step 1 and the ammonium bicarbonate solution into the reactor at a molar ratio of 1:5 at 300r / min for reaction. The flow rate of the cobalt salt solution is 3% of the volume of the reactor / h, and the reaction time is 8h. The seed particle size D50 is 4.5μm, and the particle size distribution (D90-D10) / (D90+D10) is 0.37.
[0149] 2. Growth stage: Based on step 1, the feeding reaction is continued. The flow rate of the cobalt liquid is 7% / h of the volume of the reactor. The doped cobalt liquid and the ammonium bicarbonate solution are pumped into the reactor at a molar ratio of 1:2 for reaction. When the slurry in the growth reactor reaches the upper limit, the supernatant is removed by a concentrator, and the reaction is continued until the target particle size D50 is 21.0 μm to obtain the doped cobalt carbonate slurry, which is then placed in an aging tank for temporary storage.
[0150] Step 3: Washing
[0151] The doped cobalt carbonate slurry in the aging tank is pumped into a centrifuge, and pure water is introduced for washing, and then centrifuged to dehydrate to obtain a doped cobalt carbonate wet material. The particle size distribution (D90-D10) / (D90+D10) of the cobalt carbonate in Comparative Example 1 is 0.26.
[0152] Step 4: Calcination
[0153] The doped cobalt carbonate is calcined in a rotary kiln to obtain doped cobalt tetroxide. The temperature of the high temperature zone of the rotary kiln is 800°C, and the induced wind speed in the furnace tube is 0.5m / s.
[0154] The specific parameters of the cobalt tetroxide prepared in Comparative Example 1 are shown in Table 1, and the scanning electron microscope morphology of cobalt tetroxide is shown in Figure 6 .
[0155] The cobalt trioxide obtained in Comparative Example 1 was mixed evenly with lithium carbonate at a Li / Me molar ratio of 1.05:1, and calcined at 1060° C. for 24 h to prepare the lithium cobalt oxide positive electrode material of Comparative Example 1.
[0156] Comparative Example 2
[0157] Step 1: Prepare the solution
[0158] The cobalt chloride solution and the aluminum sulfate solution are mixed to prepare an aluminum-doped cobalt salt solution, wherein the cobalt concentration in the cobalt salt solution is 110 g / L and the aluminum concentration is 1.375 g / L; and 210 g / L of ammonium bicarbonate solution is prepared.
[0159] Step 2: Synthesis of doped cobalt carbonate
[0160] 1. Opening the kettle: Add 5% of the volume of the reactor to the reactor ammonium bicarbonate solution (concentration 10g / L) as the bottom liquid. Pump the doped cobalt solution and ammonium bicarbonate solution prepared in step 1 into the reactor at a molar ratio of 1:3 at 150r / min for reaction. The flow rate of the cobalt salt solution is 1% / h of the volume of the reactor. The reaction time is 2h. The cobalt salt flow rate is 2% / h of the volume of the reactor and the reaction is continued for 2h. The seed particle size D50 is 4.6μm, and the particle size distribution (D90-D10) / (D90+D10) is 0.50.
[0161] 2. Growth stage: Based on step 1, the feed reaction is continued. The flow rate of cobalt liquid is 3% / h of the volume of the reactor. The doped cobalt liquid and ammonium bicarbonate solution are pumped into the reactor at a molar ratio of 1:2.5 for reaction. When the slurry in the growth reactor reaches the upper limit, the supernatant is removed by a concentrator. The reaction is continued until the target particle size D50 is 21.0 μm to obtain a doped cobalt carbonate slurry, which is then placed in an aging tank for temporary storage.
[0162] Step 3: Washing
[0163] The doped cobalt carbonate slurry in the aging tank is pumped into a centrifuge, and pure water is introduced for washing, and then centrifuged to dehydrate to obtain a doped cobalt carbonate wet material. The particle size distribution of the cobalt carbonate in Comparative Example 2 is (D90-D10) / (D90+D10) is 0.41.
[0164] Step 4: Calcination
[0165] The doped cobalt carbonate is calcined in a rotary kiln to obtain doped cobalt tetroxide. The temperature of the high temperature zone of the rotary kiln is 800°C, and the induced wind speed in the furnace tube is 0.5m / s.
[0166] The specific parameters of the cobalt oxide prepared in Comparative Example 2 are shown in Table 1, and the scanning electron microscope morphology of cobalt oxide is shown in Figure 7 .
[0167] The cobalt trioxide obtained in Comparative Example 2 was mixed with lithium carbonate at a Li / Me molar ratio of 1.05:1, and calcined at 1060°C for 24 hours to prepare the lithium cobalt oxide positive electrode material of Comparative Example 2. The scanning electron microscope morphology result is shown in FIG. Figure 8 shown.
[0168] The performance indicators of cobalt carbonate and cobalt trioxide in various embodiments and comparative examples are shown in Table 1.
[0169] Table 1 Performance indicators of cobalt carbonate and cobalt tetroxide
[0170]
[0171] Test example
[0172] The positive electrode materials of the above-mentioned embodiments and comparative examples were used, respectively, with conductive carbon black and polyvinylidene fluoride in a mass ratio of 85:10:5, dissolved in NMP solvent under vacuum conditions to prepare a positive electrode slurry with a weight solid content of 80%. The positive electrode disc was then prepared by coating, drying, and punching. A lithium battery was then prepared in the order of positive electrode shell-positive electrode sheet-diaphragm-negative electrode sheet-stainless steel sheet-spring sheet-negative electrode shell. The electrolyte was 1 mol / L LiPF6 / EC:DMC (volume ratio of 1:1) with 10% (volume fraction) fluoroethylene carbonate (FEC) added, and the diaphragm was a polypropylene microporous membrane. The lithium batteries of Examples 1 to 4 and Comparative Examples 1 and 2 were prepared respectively, and the battery performance of each embodiment and comparative example is shown in Table 2.
[0173] Table 2 Battery performance of each embodiment and comparative example
[0174]
[0175] According to Table 2, compared with Comparative Examples 1 and 2, the batteries of Examples 1 to 4 can improve the discharge capacity and cycle performance. This is mainly because the porosity distribution fitting R of the cobalt tetraoxide in Examples 1 to 4 is 2 The value is greater than 0.9, and the particle size distribution (D90-D10) / (D90+D10) is in the range of 0.20 to 0.35. Compared with Example 1, Example 4 has a more uniform pore distribution of cobalt oxide, and the capacity and cycle performance of the battery are improved.
[0176] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0177] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A cobalt trioxide, characterized in that: The interior of the cobalt oxide is porous, the pore distribution of the cobalt oxide is uniform, and the porosity distribution of the cobalt oxide is fitted by R 2 Value> 0.9; the particle size distribution of the cobalt oxide (D90-D10) / (D90+D10) is in the range of 0.20 to 0.35; The porosity distribution fitting R 2 The steps for validating the value are as follows: Step 1: Treat a single cobalt oxide particle as a sphere, calculate based on the cross-section circle of the sphere, and divide the circle into n concentric circles, n ≥ 3; Step 2: Calculate the area of each concentric circle and the difference between the areas of adjacent concentric circles, as well as the pore area of the corresponding area; Step 3: Calculate the change x of the cross-sectional area in different regions and the change y of the pore area in the corresponding region; Step 4: Establish a linear relationship between x and y and calculate the correlation coefficient R 2 .
2. The cobalt trioxide according to claim 1, characterized in that The pore size of the cobalt tetroxide is 1-25 nm.
3. The cobalt trioxide according to claim 1, characterized in that The particle size distribution of the cobalt oxide (D90-D10) / (D90+D10) is in the range of 0.20-0.
30.
4. The cobalt trioxide according to claim 1, characterized in that The particle size D50 of the cobalt oxide is in the range of 15 to 19 μm.
5. The cobalt trioxide according to claim 1, characterized in that The specific surface area of the cobalt tetraoxide is 2 to 4 m 2 / g.
6. The cobalt trioxide according to claim 1, characterized in that The tap density of the cobalt oxide is 2.3-2.9 g / cm 3 .
7. The cobalt tetraoxide according to any one of claims 1 to 6, characterized in that The cobalt tetroxide includes doping elements, and the total content of the doping elements is 0-3%.
8. The cobalt trioxide according to claim 7, characterized in that The doping element is selected from one or more of Al, Mg, Ni and Mn.
9. The cobalt trioxide according to claim 8, characterized in that The doping mass contents of the doping elements are respectively: Al: 0.40-1.20%, Mg: 0.10-0.50%, Ni: 0.10-3.00%, and Mn: 0.10-3.00%.
10. A cobalt carbonate, characterized in that For preparing the cobalt tetroxide according to any one of claims 1 to 9, the particle size distribution (D90-D10) / (D90+D10) of the cobalt carbonate is in the range of 0.20-0.35; and the particle size D50 of the cobalt carbonate is in the range of 19-24 μm.
11. A method for preparing cobalt carbonate, characterized in that: include: Preparing seed crystals: adding a cobalt salt solution and a precipitant solution into a reaction kettle containing a base liquid, and reacting in an intermittent production process to obtain seed crystals, wherein the particle size of the seed crystals is 4 to 6 μm, and the particle size distribution of the seed crystals (D90-D10) / (D90+D10) is in the range of 0.30 to 0.50; Seed crystal growth: on the basis of obtaining the seed crystals, continue to add the cobalt salt solution and the precipitant solution to the reactor, continue the reaction until the target particle size is reached, and obtain the cobalt carbonate slurry; Washing: washing and dehydrating the cobalt carbonate slurry to obtain the cobalt carbonate.
12. The preparation method according to claim 11, characterized in that: During the process of preparing the seed crystals, the molar ratio of the cobalt salt solution to the precipitant solution is 1:3-4.
13. The preparation method according to claim 12, characterized in that: The intermittent production process includes: firstly adding the cobalt salt solution to the reactor at a flow rate of 1% to 2% of the volume of the reactor / h to react for 2 to 4 hours, stopping feeding and stirring for 0.5 to 2 hours, and then adding the cobalt salt solution to the reactor at a flow rate of 2% to 3% of the volume of the reactor / h to continue reacting for 2 to 4 hours.
14. The preparation method according to claim 12, characterized in that: During the seed crystal growth process, the molar ratio of the cobalt salt solution to the precipitant solution is 1:2.5-3.5, and the flow rate of the cobalt salt solution is 3%-6% / h of the volume of the reactor.
15. The preparation method according to claim 11, characterized in that: The cobalt salt solution is selected from cobalt sulfate solution and / or cobalt chloride solution; the precipitant solution is selected from ammonium bicarbonate solution and / or sodium carbonate solution; and the base solution is selected from ammonium bicarbonate solution and / or sodium carbonate solution.
16. The preparation method according to claim 15, characterized in that: The cobalt concentration in the cobalt salt solution is 90-130 g / L, the concentration of the precipitant solution is 190-230 g / L; and the concentration of the base solution is 5-50 g / L.
17. The preparation method according to claim 15, characterized in that: The cobalt salt solution includes a doping element, and the doping element is selected from one or more of Al, Mg, Ni, and Mn.
18. The preparation method according to claim 17, characterized in that: The doping mass contents of the doping elements in the cobalt carbonate are respectively: Al: 0.26~0.70%, Mg: 0.06~0.33%, Ni: 0.06~2.00%, Mn: 0.06~2.00%.
19. A method for preparing cobalt trioxide, characterized in that: include: Providing the cobalt carbonate according to claim 10, or the cobalt carbonate prepared by the method for preparing cobalt carbonate according to any one of claims 11 to 18; The cobalt carbonate is sintered to obtain cobalt tetroxide.
20. The preparation method according to claim 19, characterized in that: The sintering temperature is 700-850°C.
21. The preparation method according to claim 20, characterized in that: When a rotary kiln is used for sintering, the induced air velocity in the rotary kiln tube is 0.5-5 m / s.
22. A positive electrode material, characterized in that Lithium cobalt oxide obtained by calcining the cobalt trioxide according to any one of claims 1 to 9 and a lithium source.
23. The positive electrode material according to claim 22, characterized in that The molar ratio of the lithium source to the cobalt oxide is 1-1.05; the calcination temperature is 900-1200° C., and the calcination time is 20-30 hours.
24. A lithium battery, characterized in that: Comprising the positive electrode material according to claim 22 or 23.
Citation Information
Patent Citations
Porous cobaltosic oxide nanomaterial as well as preparation method and application thereof
CN107673412A
Preparation method of large-particle narrow-distribution aluminum doped tricobalt tetroxide
CN110217832A
Cited By
Device and method for preparing cobaltosic oxide by using cobalt carbonate
CN120274538A